From rainstorms to drought - Local perspectives on climate adaptation - Ebenstål Almeida, Olivia (Nordic Africa Institute, 2023)
In Baringo County, Kenya, agro-pastoral communities are struggling for water and food security in an environment severely affected by climate change. Here is a behind-the-scenes story of a research team from the Nordic Africa Institute doing fieldwork to record local experiences of resilience, (in)equity, and the pressing need for adaptive solutions.